Vibrational spectroscopy applied to Arbutus unedo fruit spirit characterization - Antunes, Carlos Alberto Lopes (2022)
Arbutus unedo spirit (AUS) is a typical beverage of Mediterranean countries, which is usually produced without wood ageing. However, nowadays there is a trend related to the innovation and search for new market options related to this beverage. This work aimed to identify a technique to distinguish the AUS aged with different times and different toasting levels by an easier and cheaper way.